Cannabidiol on the Path from the Lab to the Cancer Patient: Opportunities and Challenges - Miguel Olivas-Aguirre; Liliana Torres-López; Kathya Villatoro-Gómez; Sonia Mayra Perez-Tapia; Igor Pottosin; Oxana Dobrovinskaya (MDPI AG, 2022)
Cannabidiol (CBD), a major non-psychotropic component of cannabis, is receiving growing attention as a potential anticancer agent. CBD suppresses the development of cancer in both in vitro (cancer cell culture) and in vivo (xenografts in immunodeficient mice) models. For critical evaluation of the advances of CBD on its path from laboratory research to practical application, in this review, we wish to call the attention of scientists and clinicians to the following issues: (a) the biological effects of CBD in cancer and healthy cells; (b) the anticancer effects of CBD in animal models and clinical case reports; (c) CBD's interaction with conventional anticancer drugs; (d) CBD's potential in palliative care for cancer patients; (e) CBD's tolerability and reported side effects; (f) CBD delivery for anticancer treatment.